The North Atlantic Waveguide and Downstream Impact Experiment - Schäfler, Andreas; Craig, Maxi; Wernli, Heini; Arbogast, Philippe; Doyle, James; Mctaggart-Cowan, Ron; Methven, John; Rivière, Gwendal; Ament, Felix; Boettcher, Maxi; Bramberger, Martin; Cazenave, Quitterie; et al. (Bulletin of the American Meteorological Society, 2018)
International audience Multi-aircraft and ground-based observations were made over the North Atlantic in fall 2016 to investigate the importance of diabatic processes for midlatitude weather.The North Atlantic Waveguide and Downstream Impact Experiment (NAWDEX) explored the impact of diabatic processes on disturbances of the jet stream and their influence on downstream high-impact weather through the deployment of four research aircraft, each with a sophisticated set of remote-sensing and in situ instruments, and coordinated with a suite of ground-based measurements. A total of 49 research flights were performed, including, for the first time, coordinated flights of the four aircraft; the German High Altitude and LOng Range Research Aircraft (HALO), the Deutsches Zentrum für Luft- und Raumfahrt (DLR) Dassault Falcon 20, the French Service des Avions Français Instrumentés pour la Recherche en Environnement (SAFIRE) Falcon 20, and the British Facility for Airborne Atmospheric Measurements (FAAM) BAe 146. The observation period from 17 Sep to 22 Oct 2016 with frequently occurring extratropical and tropical cyclones was ideal to investigate midlatitude weather over the North Atlantic. NAWDEX featured three sequences of upstream triggers of waveguide disturbances, their dynamic interaction with the jet stream, subsequent development, and eventual downstream weather impact on Europe. Examples are presented to highlight the wealth of phenomena that were sampled, the comprehensive coverage and the multi-faceted nature of the measurements. This unique dataset forms the basis for future case studies and detailed evaluations of weather and climate predictions to improve our understanding of diabatic influences on Rossby waves and downstream impact of weather systems affecting Europe.